A figure of merit for overall performance and value of AFDD tools. (February 2017) - Yuill, David P.; Braun, James E.
Highlights: A figure of merit (FOM) for automated fault detection and diagnosis tools is proposed. The FOM gives a probable monetary value for deploying an AFDD tool. There is excellent potential for value from AFDD for air-conditioners. Some tools are found to have net negative value. Fault prevalence is an important input, but is uncertain. Abstract: A figure of merit, V, to characterize the value of an AFDD maintenance tool is presented. The AFDD tool is fed data representing air-conditioners operating with and without faults across a range of conditions. The calculation of V considers the probability of each scenario occurring, the tool's response, and the resulting implications. These results are summed to give a typical average value for deploying the AFDD tool, as compared to maintenance being performed without AFDD. Case studies illustrate the calculation of V. Six AFDD tools and two idealized tools are evaluated. Five of the six real tools give negative V, meaning that their use causes more harm than good. The sixth shows approximately 10 benefit per nominal ton of air-conditioner capacity per typical maintenance visit. This represents about half of the maximum potential value. These results demonstrate the importance of measuring AFDD performance and the potential monetary benefits of AFDD.